Pengaruh Service Quality Terhadap Kepuasan Pasien Rawat Jalan di Rumah Sakit Dr. Hardjolukito Yogyakarta - Monika, Lediana; , Drs. Farid Wajdi, M.M., Ph.D; , Drs. Ahmad Mardalis, SE, MBA (2014)
The Customer loyalty is absolutely necessary in this era of increasingly fierce competition, including in the health care business. Because of the absence of customer loyalty, the hospital will not grow well even be left by customers. The purpose of this study was to analyze the affect service quality to customer satisfaction in Clinical of RS. Dr. Hardjolukito Yogyakarta .The total sample of 84 respondents in there with accidental sampling. Based on regression analysis concluded that the impact of service quality on customer satisfaction in Clinical of RS. Dr. Hardjolukito Yogyakarta ; Tangibles, Realibility and empathy effect on customer satisfaction. But the responsiveness and assurance hadn't impact to the customer satisfaction